Infection of rhesus macaques with a pool of simian immunodeficiency virus with the envelope genes from acute HIV-1 infections. Issue 1 (December 2016) - Krebs, Kendall; Tian, Meijuan; Asmal, Mohammed; Ling, Binhua; Nelson, Kenneth; Henry, Kenneth; Gibson, Richard; Li, Yuejin; Han, Weining; Shattock, Robin; Veazey, Ronald; Letvin, Norman; et al.
Abstract Background New simian–human immunodeficiency chimeric viruses with an HIV-1 env (SHIVenv) are critical for studies on HIV pathogenesis, vaccine development, and microbicide testing. Macaques are typically exposed to single CCR5-using SHIVenv which in most instances does not reflect the conditions during acute/early HIV infection (AHI) in humans. Instead of individual and serial testing new SHIV constructs, a pool of SHIVenv_B derived from 16 acute HIV-1 infections were constructed using a novel yeast-based SHIV cloning approach and then used to infect macaques. Results Even though none of the 16 SHIVenvs contained the recently reported mutations inenv genes that could significantly enhance their binding affinity to RhCD4, one SHIVenv (i.e. SHIVenv_B3-PRB926) established infection in macaques exposed to this pool. AHI SHIVenv_B viruses as well as their HIVenv_B counterparts were analyzed for viral protein content, function, and fitness to identify possible difference between SHIVenv_B3-PRB926 and the other 15 SHIVenvs in the pool. All of the constructs produced SHIV or HIV chimeric with wild type levels of capsid (p27 and p24) content, reverse transcriptase (RT) activity, and expressed envelope glycoproteins that could bind to cell receptors CD4/CCR5 and mediate virus entry. HIV-1env_B chimeric viruses were propagated in susceptible cell lines but the 16 SHIVenv_B variants showed only limited replication in macaque peripheral blood mononuclear cells (PBMCs) and 174×CEM.CCR5 cell line. AHI chimeric viruses including HIVenv_B3 showed only minor variations in cell entry efficiency and kinetics as well as replicative fitness in human PBMCs. Reduced number of N-link glycosylation sites and slightly greater CCR5 affinity/avidity was the only distinguishing feature of env_B3 versus other AHI env's in the pool, a feature also observed in the HIV establishing new infections in humans. Conclusion Despite the inability to propagate in primary cells and cell lines, a pool of 16 SHIVenv viruses could establish infection but only one virus, SHIVenv_B3 was isolated in the macaque and then shown to repeatedly infected macaques. This SHIVenv_B3 virus did not show any distinct phenotypic property from the other 15 SHIVenv viruses but did have the fewest N-linked glycosylation sites.